2017
DOI: 10.1002/ejoc.201700033
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Intermolecular Fujiwara Hydroarylation of Alkynes

Abstract: The Fujiwara hydroarylation of alkynes was reinvestigated using the addition of indole to methyl or ethyl phenylpropiolate catalyzed by Pd(OAc)2 as a model reaction. Reactions were monitored by both 1H NMR spectroscopy and electrospray ionization mass spectrometry (ESI/MS), and also through reactions carried out in the gas phase using MS/MS experiments. Contrary to the original suggestion for exclusive heteroarene activation, the data supports the coexistence of both heteroarene activation (C–H activation) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Av ery recent mechanistic investigation made on the reaction of indole with ethyl phenylpropiolate catalyzed by Pd(OAc) 2 has demonstrated that both processes depicted in Scheme 28 are operative with am arked preference for the alkyne activation at least in the adopted reaction conditions. [80] On the other hand, ap revious study on the intramolecular hydroarylation of aryl phenylpropiolates using the same catalyst in TFAh as shown as imilar trend consisting in ap reliminary alkyne activation followed by aF riedel-Crafts reaction. [81] The alkyne activation is particularly operative with Brønsted acids or metal derivatives having ar emarkable Lewis acidity.C onversely, CÀHa ctivation of indoles is very likely using some Pd II complexes or other transition metals( Ru, Rh) in the presence of ad irecting group at the nitrogen atom of the indole as previously discussed for the C-2 alkenylationsusing olefins.…”
Section: Review Hydroindolationofa Lkynes and Allenesmentioning
confidence: 98%
See 1 more Smart Citation
“…Av ery recent mechanistic investigation made on the reaction of indole with ethyl phenylpropiolate catalyzed by Pd(OAc) 2 has demonstrated that both processes depicted in Scheme 28 are operative with am arked preference for the alkyne activation at least in the adopted reaction conditions. [80] On the other hand, ap revious study on the intramolecular hydroarylation of aryl phenylpropiolates using the same catalyst in TFAh as shown as imilar trend consisting in ap reliminary alkyne activation followed by aF riedel-Crafts reaction. [81] The alkyne activation is particularly operative with Brønsted acids or metal derivatives having ar emarkable Lewis acidity.C onversely, CÀHa ctivation of indoles is very likely using some Pd II complexes or other transition metals( Ru, Rh) in the presence of ad irecting group at the nitrogen atom of the indole as previously discussed for the C-2 alkenylationsusing olefins.…”
Section: Review Hydroindolationofa Lkynes and Allenesmentioning
confidence: 98%
“…A very recent mechanistic investigation made on the reaction of indole with ethyl phenylpropiolate catalyzed by Pd(OAc) 2 has demonstrated that both processes depicted in Scheme are operative with a marked preference for the alkyne activation at least in the adopted reaction conditions . On the other hand, a previous study on the intramolecular hydroarylation of aryl phenylpropiolates using the same catalyst in TFA has shown a similar trend consisting in a preliminary alkyne activation followed by a Friedel–Crafts reaction .…”
Section: Hydroindolation Of Alkynes and Allenesmentioning
confidence: 99%
“…[7] Examples of reactions catalysed by these metals include Friedel-Crafts acylations, [8] Michael additions, [9,10] aldol condensations [11] and cycloadditions. [18,19,28,29,[20][21][22][23][24][25][26][27] Electrospray ionization mass spectrometry (ESI-MS) is a highly sensitive technique for monitoring complex reaction mixtures. [17] The growing use and applications of lanthanides as catalysts calls for detailed understanding of their speciation in solution and their reactivity modes.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently this is related to elusive unstable nature of fluoroacetylenes that could be precursors for synthesis of the such structures by hydroarylation of alkynes with indoles; a commonly used method for preparation of 3‐alkenylindoles (Scheme ). [19a], In this context, formal result of the sequence herein proposed looks like the potential reaction of indoles with fluoroacetylenes.…”
Section: Introductionmentioning
confidence: 99%